“RICH” YOUTUBER, “POOR” YOUTUBER: IMPLEMENTASI BUSINESS INTELLIGENCE DALAM MENINGKATKAN PENDAPATAN CHANNEL YOUTUBE YE - Michael Alfian Camdesus Jondar; Werner Ria Murhadi (Jurnal Abdimas Bina Bangsa, 2023)
This research is made to know the implication of Bussiness Intelligence (BI) to increase the Youtube Channel YE income. This research used a qualitative approach to get a closer look on the role of BI to improve Youtuber's income and how YE built the youtube channel from the start until now. The data source for this research comes from an interview from the Youtube Gaming YE channel owner and Youtube YE data analysis. The research findings shows that BI data implicate on how much engagement to the Youtube YE channel and increased the Youtube YE channel income